Endoplasmic reticulum stress is involved in the T‐2 toxin‐induced apoptosis in goat endometrium epithelial cells. Issue 12 (12th June 2018) - Yi, Yanglei; Zhao, Fan; Wang, Nan; Liu, Huan; Yu, Lijun; Wang, Aihua; Jin, Yaping
Abstract: T‐2 toxin is one of the trichothecene mycotoxins commonly found in animal feed and agricultural products. Ingestion of T‐2 toxin by animals results in acute and chronic diseases, as well as reproductive failure. This study aimed at investigating the role of endoplasmic reticulum (ER) stress in T‐2 toxin‐induced apoptosis in goat endometrium epithelial cells. Flow cytometry and cell viability assay showed that T‐2 toxin significantly induced cell apoptosis, which was accompanied with increased expression of cleaved‐caspase‐3. The altered expression of two ER stress markers CHOP and GRP78 proved that ER stress is involved in the T‐2 toxin‐induced apoptosis. 4‐phenylbutyrate pretreatment was applied to relieve the ER stress, pretreated endometrium epithelial cells showed a decreased apoptosis level and the expression pattern of CHOP and GRP78 was reversed. The key genes involved in signaling pathways of ER stress‐associated apoptosis were examined, which showed that the IRE1‐JNK and PERK‐ATF4‐CHOP signal transduction pathways are both activated. Moreover, the level of cytokines including interleukin (IL)‐1β, IL‐6, IL‐10 and tumor necrosis factor‐α decreased in the T‐2 toxin‐treated cells. While the 4‐phenylbutyrate pretreatment elevates the cytokine levels after T‐2 treatment. Collectively, these results suggest that ER stress contributes to the T‐2 toxin‐induced apoptosis and decreased cytokine levels in goat endometrium epithelial cells. This study offers new insight into the molecular mechanisms of T‐2 toxicity on reproductive cells. Abstract : T‐2 toxin‐induced apoptosis in goat endometrium epithelial cells is accompanied with increased expression of cleaved‐caspase‐3, and altered expression of CHOP and Grp78. The ER stress inhibitor, 4‐phenylbutyrate, decreased the apoptosis level and reversed the expression pattern of CHOP and GRP78 caused by T‐2 toxins. The IRE1‐JNK and PERK‐ATF4‐CHOP signal transduction pathways are both activated during T‐2 toxin exposure. These results indicated that ER stress is involved in T‐2 toxin‐induced apoptosis, which offers new insight into the molecular mechanisms of T‐2 toxicity on endometrium epithelial cells.